1987
DOI: 10.1118/1.596034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionization chamber construction on dose measurements in a heterogeneity

Abstract: Traditionally, measurements have been made in heterogeneous phantoms to determine the factors which should be applied to dose calculations, when calculating a dose to a heterogeneous medium. Almost all measurements have relied on relatively thin-walled ion chambers, with no attempt to match ion chamber wall material to the measuring medium. The recent AAPM dosimetry protocol has established that a mismatch between ion chamber wall and phantom material can have an effect on dose measurement. To investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Mauceri and Kase (1987) investigated the effect of mismatch of ionization chamber wall material to phantom material and demonstrated that the matching of ionization chamber wall to measuring media can be ignored provided that a small, approximately tissue-equivalent, thin-walled (≈0.1 g/cm 2 ) ion chamber is used for measuring the correction factor. [19]…”
Section: Methodsmentioning
confidence: 99%
“…Mauceri and Kase (1987) investigated the effect of mismatch of ionization chamber wall material to phantom material and demonstrated that the matching of ionization chamber wall to measuring media can be ignored provided that a small, approximately tissue-equivalent, thin-walled (≈0.1 g/cm 2 ) ion chamber is used for measuring the correction factor. [19]…”
Section: Methodsmentioning
confidence: 99%
“…ICFs are roughly determined as ratios of measured ionizations between heterogeneous and water-like media. This is possible for the lung dose correction under conditions of lateral electron equilibrium (Carrasco et al 2004, Fragoso et al 2010, Mauceri and Kase 1987, Rice et al 1988a. However, ICFs should be considered for lung under conditions of lateral electron disequilibrium (Aspradakis et al 2006, Krieger and Sauer 2005, Pisaturo et al 2012, Rice et al 1988a, Ding et al 2007a and for heterogeneous media such as bone with composition different from water (Papanikolaou et al 2004 and Boyer 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated this effect and experimental procedures were developed in order to calculate correction factors. Mauceri and Kase (1987) experimentally calculated replacement correction factors using an ionization chamber made of lung-equivalent material. Rice et al (1988) used extrapolation to obtain the reading of an ionization chamber with an infinitesimally small volume of water by fitting measurements performed for different detector volumes.…”
Section: Introductionmentioning
confidence: 99%